Acute cerebellitis following SARS‐CoV‐2 infection: A case report and review of the literature. Issue 12 (5th August 2021) - Moreno‐Escobar, Maria Camila; Feizi, Parissa; Podury, Sanjiti; Tandon, Medha; Munir, Badria; Alvi, Muhammad; Adcock, Amelia; Sriwastava, Shitiz
Abstract: Novel coronavirus disease (COVID‐19) first described in Wuhan, China in December 2019, has rapidly spread across the world and become a global public health emergency. Literature on the neurological manifestations of COVID‐19 is limited. We report a 24‐year‐old male, who presented with vertigo, dysarthria, and bradyphrenia 3 weeks after being diagnosed with COVID‐19 on nasopharyngeal reverse transcription polymerase chain reaction. The patient was diagnosed with acute cerebellitis based on magnetic resonance imaging features and showed improvement posttreatment with intravenous methylprednisone for 5 days. The scope of this article is to highlight the importance of early identification of neurological symptoms and timely management as the outcomes may be catastrophic.